The Role of Physical Education Lessons and Recesses in School Lifestyle of Adolescents - Frömel, Karel; Svozil, Zbyněk; Chmelík, František; Jakubec, Lukáš; Groffik, Dorota (The Journal of school health, 2016)
BACKGROUND: This study investigates school lifestyle among adolescents in terms of physical activity (PA) structure: (1) adolescents participating in a physical education lesson (PEL) versus (2) aggregate recess time exceeding 60 minutes. METHODS: The research was conducted in 24 secondary schools in the Czech Republic (boys N = 208, girls N = 433). For the whole day (1-3 days) participants wore the ActiTrainer accelerometer, which monitored PA, and heart rate. A total of 1122 school days were recorded. RESULTS: Both boys and girls participating in a PEL reported significantly better results compared with nonparticipating individuals regarding all indicators of volume and intensity of school PA (SPA). In most SPA indicators, longer aggregate recess time (>60 minutes) had a statistically significant effect, particularly on the volume of SPA. The recommended 500 steps/hours for SPA was achieved by 83% of boys participating in PEL and 69% of girls. In contrast just 32% of nonparticipating boys and 31% of girls reached this level. With longer recess time the recommendation was met by 43% of boys (42% of girls) compared with 26% of boys (23% of girls) with shorter recess time. CONCLUSIONS: An increase in SPA and an improved lifestyle in adolescents on school days are significantly supported more by PELs than by longer recess time.
Keywords: Sedentary Behavior; Adolescent Behavior; recess; Analysis of Variance; studenti; Physical Education and Training; Male; physical education; Basal Metabolism; bazální metabolismus; rekreace; Guideline Adherence; Adolescent; Česká republika; zdravotní politika; rozložení podle pohlaví; akcelerometrie; mužské pohlaví; Exercise; Sex Distribution; mladiství; Czech Republic; tělesná výchova; Schools; školy; lidé; sedavý životní styl; ženské pohlaví; analýza rozptylu; Students; dodržování směrnic; Humans; school physical activity; pohybová aktivita; Motor Activity; Accelerometry; Female; health education; cvičení; Health Policy; Recreation; youth lifestyle; chování mladistvých